Patterns and Determinants of Disability in Older Populations of Nepal - Thapa, Naba Raj; Karki , Rita Devi (Tribhuvan University Journal, 2025)
Disability is a critical issue of human condition and poses a increasing health concern in the context of rapidly aging population in Nepal. The aim of this paper is to assess the prevalence of disability and examine the factors associated with disability among older people in Nepal. Microdata samples from the 2021 National Population and Housing Census, including 296,256 individuals aged 60 years and above were analyzed using multivariable log-binomial regression. Disability prevalence was 7.6 percent. Physical disability most common disability accounted for 2.2 percent of older people, followed by low vision. Older people aged 85 years and above had an 89% higher prevalence of disability (aPR=1.89). Females reported a 22% lower prevalence of disability (aPR=0.78). Older people in the Terai had a 23% higher prevalence of disability (aPR=1.23) and those in Gandaki province had a 28% higher prevalence (aPR=1.28), whereas those in Madhesh province had a 26% lower prevalence of disability (aPR=0.74). The prevalence of disability was 15% higher in rural residents (aPR=1.15), 14% higher among Mountain/Hill Janajati (aPR=1.14)) and 19% higher among Hill Dalits (aPR=1.19). Conversely, the prevalence of disability was 22% lower among Madhesh/Terai caste (aPR=0.78) and Madhesh/Terai Dalits (aPR=0.78). Older people who belonged to Kirat had a 12% higher (aPR=1.12) and Christians had 21% higher (aPR=1.21) prevalence of disability. Married older people had a 24% lower prevalence (aPR=0.76). The prevalence of disability was 19% lower among older people with primary education (aPR=0.81), 31% lower with secondary (aPR=0.69), and 48% lower with higher education (aPR=0.52). Older people from the richest households had a 38% lower disability prevalence (aPR=0.62). These findings indicate the structural inequalities influencing disability among older people in Nepal and emphasize the need for health and social policies to reduce disparities and promote healthy and active aging.